Safety and immunogenicity of the Rift Valley fever arMP-12 ΔNSm21/384 candidate vaccine in pregnant ewes. (11th December 2020) - Boumart, Z.; Bamouh, Z.; Hamdi, J.; Safini, N.; Tadlaoui, K.O.; Bettinger, G.; Watts, D.M.; Elharrak, M.
Highlights: Rift Valley fever virus causes abortion, teratogenicity and mortality in domestic ruminants. Safety and immunogenicity RVFV arMP-12ΔNSm21/384 vaccine was determined in pregnant ewes. Vaccine was safe and immunogenic last stages of pregnancy, but may caused malformed lambs early stage. Pregnant sheep should not be vaccinated with the RVFV vaccine during the first month of gestation. Abstract: Rift Valley fever (RVF) poses a threat to human and animal health as well as economic losses due to abortion, new-born teratogenic effect and mortality. Safe and effective vaccines are critically needed to prevent the disease in humans and livestock. The objective of this study was to assess safety and immunogenicity of the Rift Valley fever virus (RVFV) arMP-12DNSm21/384 attenuated vaccine in 32 pregnant ewes at different stages of pregnancy including 17 ewes vaccinated during the early stage (G1) of pregnancy (<35 days) and 15 ewes vaccinated during the last two stages (G2) of pregnancy (>35 days). Ewes were monitored for clinical observations, rectal temperature and abortions and lambs were monitored for general health and rectal temperature. Vaccinated ewes and lambs were periodically sampled for their neutralizing antibody response to RVFV vaccination. All ewes were positive for antibody two weeks post-vaccination and 79% of ewes were positive at delivery. None of the 32 ewes aborted during pregnancy and all ewes vaccinated during the G2 stages of pregnancy gave birth to healthy lambs. However, among the 17 ewes vaccinated during the G1 stage of pregnancy, 2 ewes gave birth to 2 lambs with fore limb malformations that died at 1-day of age. One ewe gave birth to 2 punny twins that died at 2 days of age. Another ewe, gave birth to one lamb with a deformed tail that died at 20 days of age. At post-mortem, tissues of dead lambs (spleen, lung, brain and long bone) were negative for RVFV by PCR assay. While the findings did not link the malformed lambs directly to infection by the vaccine virus, these results indicated that pregnant sheep should not be vaccinated with the RVFV arMP-12DNSm21/384 vaccine during the first month of gestation.